2010
DOI: 10.2533/chimia.2010.188
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Cyclopropanations via Sequential Atom Transfer Radical Addition-Dechlorination Reactions

Abstract: In organic synthesis, cyclopropanation reactions are often performed with Simmons-Smith-type reagents or by transition metal catalyzed reactions of olefins with diazo compounds. A novel method for the synthesis of substituted cyclopropanes is described that is based on a two-step reaction sequence. Olefins are reacted with 1,1'-dichlorides in a Ru-catalyzed atom transfer radical addition (ATRA) process and the resulting 1,3-dichlorides are directly converted into cyclopropanes by reductive coupling with magnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The reaction originates from the Kharasch addition, , and it is typically catalyzed by transition metal complexes of copper or ruthenium. Traditionally, ATRA required rather large amounts of metal catalyst to achieve high chemoselectivity toward the desired single addition adduct. However, the use of reducing agents such as free radicals generated by thermal or photodecomposition of diazo initiators (2,2′-azobis(2-methylpropionitrile) (AIBN) and 2,2′-azobis(4-methoxy-2,4-dimethyl valeronitrile) (V-70)), magnesium, or environmentally benign ascorbic acid , successfully circumvented this problem. As a result, this organic transformation can now be conducted using very low amounts of the metal. ,− ATRA has long been accepted to involve free radical intermediates. , Shown in Scheme is the proposed mechanism for copper catalyzed ATRA in the presence of reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction originates from the Kharasch addition, , and it is typically catalyzed by transition metal complexes of copper or ruthenium. Traditionally, ATRA required rather large amounts of metal catalyst to achieve high chemoselectivity toward the desired single addition adduct. However, the use of reducing agents such as free radicals generated by thermal or photodecomposition of diazo initiators (2,2′-azobis(2-methylpropionitrile) (AIBN) and 2,2′-azobis(4-methoxy-2,4-dimethyl valeronitrile) (V-70)), magnesium, or environmentally benign ascorbic acid , successfully circumvented this problem. As a result, this organic transformation can now be conducted using very low amounts of the metal. ,− ATRA has long been accepted to involve free radical intermediates. , Shown in Scheme is the proposed mechanism for copper catalyzed ATRA in the presence of reducing agents.…”
Section: Introductionmentioning
confidence: 99%
“…31 For the same system, further dehalogenation in the presence of magnesium also resulted in the formation of functionalized cyclopropanes. 32, 33 The research groups of Pérez 34 and Pintauer 17 have recently reported coppercatalyzed sequential process in which 1,6-dienes were converted to cyclopentanes via ATRA followed by sequential ATRC. 1,6-Dienes were chosen for the study because the addition of radicals generated by the homolytic cleavage of the alkyl halide bond resulted in the formation of 5-hexenyl radicals, which are known to undergo very fast and selective 5-exo-trig mode of cyclization.…”
Section: Sequential Atom Transfer Radical Addition (Atra) and Cycliza...mentioning
confidence: 99%